THE ANALYSIS OF TECHNICAL GUIDANCE PROGRAM FOR CAPACITY BUILDING ENHANCEMENT FOR THE MEMBERS OF BENGKAYANG REGENCY LEGISLATIF BOARD - B11106229, ELISABET PONDOK (Jurnal Manajemen Update, 2013)
The title of this minithesis is The Analysis of Technical Guidance Program for Capacity Building Enhancement for The Members of Bengkayang Regency Legislatif Board, while the analysis aimed to find out how far it is the quility work enhancement of the members after joining the technical guidence program. The method used in the analysis is descriptive method namely problem solving procedure done by describing current situation and condition based on facts, data, symptom and phenomena. The technique of data gathering done by observing, questionnair disseminating and documenting. The data gathered then analysed descriptively namely by analysing the result of questionnair analysis which then percentaged and concluded based on respondents answers. The result of the analysis concludes that based on the gendre characteristic the respondents are mainly male which is 90%, based on age range the respondents mainly come from the range of age of 30 to 40s years old which are 40%, based on the educational degree the respondents mainly come from S1 degree of education, while based on period of joining the legislatif membership the respondents mainly have the period of membership which have been 5 years membership which are 76.67%. Therefore, the activity of the program which have been done expected to enhance the quality of work of the legislatif members. Of the analysis on 8 sub variables namely loyalty, work performance, responsibility, lawfulness, honesty, cooperation, initiative and leadership there found out the total score of 2,123 and the average number of 106.15 which is classified High/good. However, on the sub varible of loyalty with the members loyalty indicator to their work the analysis has found out that the score comes to 95 which is categorized adequate. The other adequate categories have also been found out on the sub variables loyalty with the indicator of timeliness and on the sub variable honesty. Key Word: Technical Guidance Program / Legislatif members training